Intended and unintended consequences of the implementation of minimum unit pricing of alcohol in Scotland: a natural experiment - Vivian So; Andrew D Millard; S Vittal Katikireddi; Ross Forsyth; Sarah Allstaff; Paolo Deluca; Colin Drummond; Allison Ford; Douglas Eadie; Niamh Fitzgerald; Lesley Graham; Shona Hilton; et al. (NIHR Journals Library, 2021)
Background: Scotland was the first country to implement minimum unit pricing for alcohol nationally. Minimum unit pricing aims to reduce alcohol-related harms and to narrow health inequalities. Minimum unit pricing sets a minimum retail price based on alcohol content, targeting products preferentially consumed by high-risk drinkers. This study comprised three components. Objectives: This study comprised three components assessing alcohol consumption and alcohol-related attendances in emergency departments, investigating potential unintended effects of minimum unit pricing on alcohol source and drug use, and exploring changes in public attitudes, experiences and norms towards minimum unit pricing and alcohol use. Design: We conducted a natural experiment study using repeated cross-sectional surveys comparing Scotland (intervention) and North England (control) areas. This involved comparing changes in Scotland following the introduction of minimum unit pricing with changes seen in the north of England over the same period. Difference-in-difference analyses compared intervention and control areas. Focus groups with young people and heavy drinkers, and interviews with professional stakeholders before and after minimum unit pricing implementation in Scotland allowed exploration of attitudes, experiences and behaviours, stakeholder perceptions and potential mechanisms of effect. Setting: Four emergency departments in Scotland and North England (component 1), six sexual health clinics in Scotland and North England (component 2), and focus groups and interviews in Scotland (component 3). Participants: Research nurses interviewed 23,455 adults in emergency departments, and 15,218 participants self-completed questionnaires in sexual health clinics. We interviewed 30 stakeholders and 105 individuals participated in focus groups. Intervention: Minimum unit pricing sets a minimum retail price based on alcohol content, targeting products preferentially consumed by high-risk drinkers. Results: The odds ratio for an alcohol-related emergency department attendance following minimum unit pricing was 1.14 (95% confidence interval 0.90 to 1.44; p = 0.272). In absolute terms, we estimated that minimum unit pricing was associated with 258 more alcohol-related emergency department visits (95% confidence interval -191 to 707) across Scotland than would have been the case had minimum unit pricing not been implemented. The odds ratio for illicit drug consumption following minimum unit pricing was 1.04 (95% confidence interval 0.88 to 1.24; p = 0.612). Concerns about harms, including crime and the use of other sources of alcohol, were generally not realised. Stakeholders and the public generally did not perceive price increases or changed consumption. A lack of understanding of the policy may have caused concerns about harms to dependent drinkers among participants from more deprived areas. Limitations: The short interval between policy announcement and implementation left limited time for pre-intervention data collection. Conclusions: Within the emergency departments, there was no evidence of a beneficial impact of minimum unit pricing. Implementation appeared to have been successful and there was no evidence of substitution from alcohol consumption to other drugs. Drinkers and stakeholders largely reported not noticing any change in price or consumption. The lack of effect observed in these settings in the short term, and the problem-free implementation, suggests that the price per unit set (£0.50) was acceptable, but may be too low. Our evaluation, which itself contains multiple components, is part of a wider programme co-ordinated by Public Health Scotland and the results should be understood in this wider context. Future work: Repeated evaluation of similar policies in different contexts with varying prices would enable a fuller picture of the relationship between price and impacts. Trial registration: Current Controlled Trials ISRCTN16039407. Funding: This project was funded by the National Institute for Health Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 9, No. 11. See the NIHR Journals Library website for further project information.